2002
DOI: 10.1590/s0074-02762002000300025
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the Oviposition Preferences of Aedes aegypti in Function of Substratum and Humidity

Abstract: 1981and 1998(Teixeira et al. 1999, after decades of absence (Schatzmayr 2000). The ovipositing habit of this mosquito is still little understood. In the case of Brazil, the few studies on the ovipositing behaviour of this insect were conducted on a population that has already been eradicated, and the current population may be of a different origin, thus not presenting the same behaviour as observed previously. Variations have been observed in terms of life span and the number of eggs produced by females of 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 7 publications
2
34
1
3
Order By: Relevance
“…Rainfall is assumed to affect positively the fraction of eggs that successfully hatch (cv) (Alto and Juliano, 2001; Rossi et al, 2015; Tran et al, 2013; Madeira et al, 2002). A similar positive relationship is taken for the vector biting rate (av) and humidity levels (Yasuno and Tonn, 1970), in contrast to a negative effect on the adult mosquito mortality rate (μVv) (Alto and Juliano, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Rainfall is assumed to affect positively the fraction of eggs that successfully hatch (cv) (Alto and Juliano, 2001; Rossi et al, 2015; Tran et al, 2013; Madeira et al, 2002). A similar positive relationship is taken for the vector biting rate (av) and humidity levels (Yasuno and Tonn, 1970), in contrast to a negative effect on the adult mosquito mortality rate (μVv) (Alto and Juliano, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…The CCA revealed that a high level of atmospheric humidity, most likely maintained by the vegetation cover on the bank, was a factor supporting Coquillettidia female choice. This factor is not specific to Coquillettidia species, and it is an ecological parameter involved in the selection of oviposition site for several mosquito species such as Aedes (Madeira et al, 2002) and Toxorhynchites (Jordan, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that this paddle rejection might be due to the presence of kairomone left by predators or natural enemies such as ants or cockroaches, or the eggs might have been attacked by these predators while they were on the paddles. Madeira et al (12) witnessed this incidence in the fi eld, and this event might likely be quite common in nature. Soares et al (15) also found eggs only in the water, but at a lower percentage (23 of 500 surveys = 4.6%).…”
mentioning
confidence: 91%
“…Soares et al (15) found 11.2% of all eggs in the water in 96% of the fi eld traps and reported signifi cant increase in the number of eggs in the water when the relative humidity dropped below 40%. In the laboratory, Madeira et al (12) also showed that, at lower humidity, females oviposited more eggs on the liquid surface. Gomes et al (13) conducted a laboratory experiment and indicated that eggs oviposited on water surface showed faster eclosion and argued that this particularity in the environment could lead to faster colonization.…”
mentioning
confidence: 98%
See 1 more Smart Citation